Biovalorization of Soy Milk By-product Flour Using Controlled Fermentation: Physical Characteristics Perspective - Putu Tessa Fadhila; Ade Galuh Rakhmadevi; Frengky Hermawan Hadi Prasetyo; Rasmiyana Rasmiyana; Putri Satika Dewi (P3M Politeknik Negeri Jember, 2026)
Okara, a byproduct of soymilk production, contains high dietary fibre (58.6%) but is underutilized. This study evaluates fermentation as a biovalorization strategy to produce functional okara flour. The novelty lies in comparing spontaneous fermentation with commercial yeast under controlled durations to identify optimal conditions for flour production. Fresh okara was fermented using two commercial yeasts and spontaneous fermentation for 3 and 4 days. The fermented material was dried, milled into flour, and analysed for yield (%), colour (L*, a*, b*, whiteness index), and particle size (µm). The experiment followed a two-factor Completely Randomized Design (CRD), with data analysed using ANOVA and Duncan’s Multiple Range Test (DMRT). Fermentation method and duration significantly affected flour properties. The best treatment was 3-day spontaneous fermentation, producing 11.7% yield with L* = 70.88, a* = 0.338, b* = 11.061, and a whiteness index of 68.82. The flour exhibited a fine particle size of 35.23 µm, indicating good suitability for food applications. These results demonstrate that short-duration spontaneous fermentation can produce okara flour with favourable physical characteristics without requiring commercial starters. This approach provides a simple, cost-effective, and scalable method for developing fibre-rich functional ingredients. Further optimization may enhance quality and expand its application in food products.